Evaluation of Organic and Vermi Composts for Mass Culturing of Trichoderma Harzianum to be Used Against Soil-Borne Pathogen Sclerotium Rolfsii of Groundnut - Iqbal Faruk (Journal of Agronomy Research, 2021)
The experiments were conducted in the fields of Plant Pathology Division, Bangladesh Agricultural Research Institute, Gazipur during 2016-17, 2017-18 and 2018-19 cropping years to evaluate the organic and vermi composts for mass culturing of biological control agent Trichoderma harzianum and toobserve the effect of formulated T.harzianum designated as Tricho-vermi-compost and Tricho-organic-compost as well as organic compost, vermi-compost and chemical fungicide Provax 200 WP against soil-borne pathogens, Sclerotium rolfsiiof groundnut causing foot and root rot/stem rot disease. The pathogen inoculated field soils were treated with Tricho-vermi-compost and Tricho-organic-compost, organic compost and vermi-compost 7 days before seed sowing where as seeds were treated with Provax 200 WP at the time of seed sowing. From this study it was revealed that all the treatments performed in reducing seedling mortality and increasing plant growth and yield of groundnut compared to control. Among the treatments, soil treatment with Tricho-vermi-compost and Tricho-organic-compost are the best treatments in reducing seedling mortality and increasing plant growth parameters and yield of groundnut which was significantly differed from the other treatments including control. Seed treatment with chemical fungicide Provax 200 WP and soil treatment with only vermin-compost and organic compost also promising treatments for management foot and root rot disease and increasing plant growth parameters as well as yield of groundnut compared to control.
Keywords: Groundnut